Using of a Spoof Text to Develop Speaking Skill by Instagram at the Eleventh Grade of State Senior High School 1 Selesai in Academic Year 2022/2023 - Umi Aini; Ayu Indari; afdhalina, afdhalina (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2023)
The research aimed to find out a using of spoof text to develop speaking skill by Instagram at the eleventh grade of State Senior High School 1 Selesai. The subjects were all students in eleventh grade that is XI Mathematics and Natural Sciences Department 2 with a population 32 of students and 30 students were chosen as the sample.  This study was qualitative descriptive research. This study used observation, and documentation as a technique for collecting data. The data was collected using a video WhatsApp group actually post in Instagram with group discussion in two member of a group and the video will take one by one. The results of research at State Senior High School 1 Selesai  are the most important for teachers to evaluate learning methods by using of a spoof text to develop speaking skill by social media Instagram so that students can understand the learning material well in accordance with the expectations of each individual.